Unusual eosinophilia not detected by an automated haematological analyser in a patient with liver cirrhosis. - Kabutomori, O (1997)
The use of automated haematological analysers to differentiate leucocytes has become more widespread. Unusual eosinophilia in a 57 year old man with liver cirrhosis, caused by hepatitis C infection, and abnormal blood counts detected using a manual method (eosinophils, 50%) was not detected by an automated analyser using the electrical impedance method (0.3%) or the optical method (14.1%). It is important to check blood films when cell counts are apparently abnormal, even for automated haematological examination.